High-film-thickness anti-cracking high-solid anticorrosive paint and preparation method thereof
By using epoxy resin, polyenol glycidyl ether compound, alkali-free glass fiber powder and anti-rust filler in high film thickness anti-corrosion coatings, combined with epoxy curing agent and modified phenoamine curing agent, the problems of cracking and shrinking of traditional coatings under low temperature conditions are solved, and a coating with high solid content, low VOCs, and good crack resistance is achieved.
Patent Information
- Application Number
- CN202411874633.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional high-film-thick anticorrosion coatings are prone to cracking and shrinking holes under low temperature conditions, and have low solid content and high VOCs content, which affects its adhesion and mechanical properties.
Component A and component B are used to combine. Component A includes epoxy resin, polyenol glycidyl ether compound, alkali-free glass fiber powder and anti-rust filler. Component B includes epoxy curing agent and modified phenoamine curing agent. It is dispersed evenly through a high-speed disperser to improve the solid content and cracking resistance.
It has achieved high film thickness and anti-sagging, good corrosion resistance and salt spray resistance, high hardness and high adhesion, excellent crack resistance under low temperature conditions, and is suitable for marine engineering steel structures, chemical machinery and equipment and long conveying pipelines.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical materials, and in particular to a high-thickness, crack-resistant, high-solid anticorrosive coating and a preparation method thereof. Background Art
[0002] High film thickness epoxy resin coatings can be widely used in various harsh environments, and are used to protect steel structures and equipment when high wear resistance and anti-corrosion requirements are required, such as splash zones of offshore oil and gas platforms and bridges, docks, breakwaters and chemical plants. Traditional high film thickness anti-corrosion coatings such as thick paste epoxy paints and epoxy coal tar anti-corrosion coatings have the disadvantages of high volatile organic compounds (VOCs), slow film formation and curing, easy cracking at low temperatures and poor adhesion during high film thickness construction. Therefore, the toxicity of solvents can be reduced by increasing the solid content of the coating, and the volume shrinkage is small after low temperature curing, with good adhesion and mechanical properties, but there are also problems such as easy cracking and more shrinkage holes under low temperature conditions.
[0003] The invention patent with publication number CN 118308006 A discloses an anti-corrosion coating suitable for offshore photovoltaic trusses and a preparation method thereof. The main film-forming material of the anti-corrosion coating is nano zinc oxide modified epoxy resin; component B is a polyamide curing agent, an anti-aging agent, and a solvent. While meeting the anti-corrosion requirements of offshore photovoltaic trusses, the anti-corrosion coating can improve the weather resistance of epoxy thick paste coatings, so that there is no obvious yellowing and powdering during the storage process of up to half a year to a year. However, adding silica powder as a thixotropic agent to the epoxy-modified amine system will affect the transparency and glossiness of the coating, thereby limiting the scope of use of the epoxy system coating. At the same time, the coating system resin uses nano zinc oxide modified epoxy resin, and the high cost will also affect large-scale application.
[0004] The invention patent with publication number CN 114479607 A discloses a high-performance epoxy modified thick paste coating applied to the surface of steel structures. It is a two-component, high-solid thick paste modified epoxy shielding coating that can provide long-term protection with a single coat. However, the film thickness of the coating after curing is about 800μm, which limits the use of this coating system in high film thickness application fields. At the same time, the high VOCs content is prone to cause shrinkage holes or even cracking problems, and carbon fiber powder is also prone to environmental pollution. The solid content still needs to be further increased to meet the more stringent environmental protection limit index requirements.
[0005] Therefore, how to increase the solid content in the coating and overcome the problem of low-temperature cracking during the construction of traditional high-film thickness anti-corrosion coatings is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention
[0006] In order to overcome the problems existing in the prior art, the present invention provides a high-thickness, crack-resistant, high-solid anti-corrosion coating, which comprises a component A and a component B, measured by weight, wherein the component A comprises 24-28 parts of epoxy resin, 6-8 parts of polyphenol glycidyl ether compound, 2.8-3.6 parts of auxiliary agent, 3.6-4.8 parts of alkali-free glass fiber powder, 37-41 parts of rust-proof filler and 3-4 parts of solvent; the component B comprises 10.1-10.9 parts of epoxy curing agent and 4.3-4.7 parts of modified phenolic amine curing agent.
[0007] On the basis of the above scheme, further, the epoxy resin is E-51 bisphenol A epoxy resin, and its epoxy equivalent is 190-200.
[0008] On the basis of the above scheme, further, the polyphenol glycidyl ether compound is prepared by reacting plant polyphenols with oxirane in the presence of a quaternary ammonium salt catalyst; the epoxide equivalent of the polyphenol glycidyl ether compound is 280-320.
[0009] On the basis of the above scheme, further, the auxiliary agent includes 0.36-0.44 parts of defoaming agent, 0.27-0.33 parts of dispersant, 0.45-0.55 parts of rheological additive, and 1.8-2.2 parts of thixotropic agent.
[0010] Preferably, the auxiliary agent includes 0.4 parts of defoaming agent, 0.3 parts of dispersant, 0.5 parts of rheological auxiliary agent and 2 parts of thixotropic agent.
[0011] On the basis of the above scheme, further, the defoaming agent is one or more combinations of vegetable oil defoaming agent and silicone defoaming agent; the dispersant is one or more combinations of BYK-180, BYK-190, Euka 690w, SN5040, and X-405; the rheological additive is organic bentonite; and the thixotropic agent is a polyamide thixotropic agent.
[0012] On the basis of the above scheme, further, the mesh size of the alkali-free glass fiber powder is 200-300 meshes, and the aspect ratio is 4-8:1.
[0013] Preferably, the alkali-free glass fiber powder is a material obtained by precisely chopping and wet-grinding alkali-free glass raw fibers to remove impurities and screen them.
[0014] On the basis of the above scheme, further, the anti-rust filler is prepared by mixing 15-16 parts of iron titanium powder, 12-13 parts of talc powder, 3-4 parts of precipitated barium sulfate and 7-8 parts of titanium dioxide in parts by weight.
[0015] Preferably, the iron titanium powder comprises 15 parts, talc powder comprises 12 parts, precipitated barium sulfate comprises 3 parts and titanium dioxide comprises 7 parts.
[0016] The purpose of adopting the above technical scheme is that ferrotitanium powder has excellent anti-corrosion performance, high specific gravity and environmental protection advantages; the addition of titanium dioxide can improve the whiteness, tinting power, heat resistance, chemical stability and non-toxicity of the coating; precipitated barium sulfate has the characteristics of strong chemical inertness, good stability, acid and alkali resistance, and moderate hardness.
[0017] On the basis of the above scheme, further, the solvent is a mixture of xylene and n-butanol in a mass ratio of 1.5-2.0:1.5-2.0.
[0018] Preferably, the mass ratio of xylene to n-butanol is 1:1.
[0019] The present invention also provides a method for preparing the high-thickness, anti-cracking, high-solid anti-corrosion coating as described above, comprising the following steps: The preparation process of the component A is as follows: S1, adding epoxy resin, polyphenol glycidyl ether compound, solvent and defoamer, dispersant and rheological additive in proportion, stirring at a high speed of 1200-1500r / min for 15-20min by a high-speed disperser to evenly disperse the raw materials; S2. Add anti-rust filler and disperse at high speed at 3000-3200r / min for 30-40min; S3. Add alkali-free glass fiber powder and continue dispersing at 3000-3200r / min for 20-30min; S4, add thixotropic agent, disperse at 1200-1500r / min for 10-15min; S5, test fineness, viscosity, filter and package; The preparation process of the component B is as follows: S1. Add epoxy curing agent and modified phenolic amine curing agent in proportion, and disperse them evenly at 600-800r / min for 15-20min using a high-speed disperser; S2. Check viscosity and density, and packaging is completed.
[0020] The present invention also provides a high-thickness, crack-resistant, high-solid anti-corrosion coating for use in marine engineering steel structures, chemical machinery and equipment, and long transmission pipelines, wherein the mass ratio of component A to component B is 7.9-8.5:1.
[0021] Compared with the prior art, the high-film thickness, crack-resistant, high-solid anti-corrosion coating provided by the present invention mixes epoxy resin, polyphenol glycidyl ether compound and alkali-free glass fiber powder in a certain proportion, uses epoxy curing agent and modified phenolic amine curing agent in a certain proportion as a curing agent system, and then adds anti-rust fillers and additives. This makes the coating of the present invention have high solid content and low VOCs content, can achieve the effect of high film thickness anti-sagging and good corrosion resistance and salt spray resistance, has high hardness and high adhesion, and has excellent crack resistance under low temperature conditions. It is suitable for marine engineering steel structures, chemical machinery and equipment, long transmission pipelines and other scenes that require high film thickness anti-corrosion and harsh outdoor environment temperatures. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In order to more fully illustrate the beneficial effects of the present invention, the present invention provides the following embodiments and comparative examples: Example 1 A high-thickness, crack-resistant, high-solid anticorrosive coating, comprising component A and component B, wherein, by weight, the component A comprises 24 parts of epoxy resin, 8 parts of polyphenol glycidyl ether compound, 3.2 parts of auxiliary agent, 4.2 parts of alkali-free glass fiber powder, 37 parts of rust-proof filler, and 3 parts of solvent; the component B comprises 10.1 parts of epoxy curing agent and 4.3 parts of modified phenolic amine curing agent; Wherein, the epoxy resin is E-51 bisphenol A epoxy resin, and the epoxy equivalent is 190-200; The additives include 0.4 parts of defoamer, 0.3 parts of dispersant, 0.5 parts of rheological additive, and 2 parts of thixotropic agent; The defoamer is an organosilicon defoamer; the dispersant is BYK-180; the rheological additive is organic bentonite; and the thixotropic agent is a polyamide thixotropic agent; The anti-rust filler is prepared by mixing 15 parts of iron titanium powder, 12 parts of talc powder, 3 parts of precipitated barium sulfate and 7 parts of titanium dioxide; The solvent is a mixture of xylene and n-butanol in a mass ratio of 1:1; The preparation process of Example 1 is as follows: The preparation process of the component A is as follows: S1, adding epoxy resin, polyphenol glycidyl ether compound, solvent and defoamer, dispersant and rheological additive in proportion, stirring at a high speed of 1200-1500r / min for 15-20min by a high-speed disperser to evenly disperse the raw materials; S2. Add anti-rust filler and disperse at high speed at 3000-3200r / min for 30-40min; S3. Add alkali-free glass fiber powder and continue dispersing at 3000-3200r / min for 20-30min; S4, add thixotropic agent, disperse at 1200-1500r / min for 10-15min; S5, test fineness, viscosity, filter and package; The preparation process of the component B is as follows: S1. Add epoxy curing agent and modified phenolic amine curing agent in proportion, and disperse them evenly at 600-800r / min for 15-20min using a high-speed disperser; S2. Check viscosity and density, and packaging is completed.
[0024] Example 2 The difference between Example 2 and Example 1 is that the ratio of component A is different, and the ratio of other raw materials and the preparation process are the same as those of Example 1; The specific proportion of component A is as follows: by weight, it includes 24 parts of epoxy resin, 8 parts of polyphenol glycidyl ether compound, 3.2 parts of auxiliary agent, 3.6 parts of alkali-free glass fiber powder, 37 parts of rust-proof filler and 3 parts of solvent.
[0025] Example 3 The difference between Example 3 and Example 1 is that the component ratio of component A and component B is different, and the other raw material ratios and preparation process are the same as those of Example 1; The specific ratio of component A and component B is: component A includes 28 parts of epoxy resin, 6 parts of polyphenol glycidyl ether compound, 3.6 parts of auxiliary agent, 4.8 parts of alkali-free glass fiber powder, 41 parts of anti-rust filler, and 4 parts of solvent; The additives include 0.5 parts of defoamer, 0.4 parts of dispersant, 0.6 parts of rheological additive, and 2.1 parts of thixotropic agent; Component B includes 10.9 parts of epoxy curing agent and 4.7 parts of modified phenolic amine curing agent.
[0026] Comparative Example 1 The specific component ratio of the high-film thickness anti-cracking type high-solid anti-corrosion coating of Comparative Example 1 is: In terms of weight, the component A comprises 28 parts of epoxy resin, 0 parts of polyphenol glycidyl ether compound, 3.6 parts of auxiliary agent, 4.8 parts of alkali-free glass fiber powder, 41 parts of rust-proof filler, and 4 parts of solvent; the component B comprises 9.6 parts of epoxy curing agent and 4.1 parts of modified phenolic amine curing agent; the remaining raw material ratios and preparation process are the same as those in Example 1; The auxiliary agent includes 0.5 parts of defoaming agent, 0.4 parts of dispersant, 0.6 parts of rheological auxiliary agent and 2.1 parts of thixotropic agent.
[0027] Comparative Example 2 The specific component ratio of the high-film thickness anti-cracking type high-solid anti-corrosion coating of Comparative Example 2 is: In terms of weight, the component A includes 24 parts of epoxy resin, 8 parts of polyphenol glycidyl ether compound, 3.6 parts of auxiliary agent, 0 parts of alkali-free glass fiber powder, 41 parts of rust-proof filler, and 4 parts of solvent; the component B includes 10.1 parts of epoxy curing agent and 4.3 parts of modified phenolic amine curing agent; the remaining raw material ratios and preparation process are the same as those in Example 1; The auxiliary agent includes 0.5 parts of defoaming agent, 0.4 parts of dispersant, 0.6 parts of rheological auxiliary agent and 2.1 parts of thixotropic agent.
[0028] The specific components and addition amounts of the embodiments and comparative examples provided by the present invention are shown in Table 1: Table 1
[0029] Performance Test: The components A and B of Examples 1-3 and Comparative Examples 1-2 were mixed uniformly according to the mass ratio of the formula in the table, and then the components A and B were mixed at a mass ratio of 8:1, and the coating was prepared by high-speed dispersion, and its physical properties were tested, and the sample was sprayed on a steel plate sandblasted to sa2.5 grade (the dry film thickness of the resistance test such as acid resistance and salt spray resistance was 250 μm, and the test was performed after curing for 7 days at room temperature). The test results are shown in Table 2.
[0030] Table 2 Performance test results
[0031] It can be seen from Table 2 that, compared with Examples 1 and 2, after the main resin of Comparative Example 1 is changed from the epoxy resin-polyphenol glycidyl ether compound system to the single E-51 resin system, the resulting coating not only has a slower drying speed, a lower sag performance, but also a lower salt spray resistance and acid resistance; compared with Examples 1 and 2, the coating obtained in Comparative Example 2 without adding alkali-free glass fiber powder has a slower drying speed, a lower sag performance, a lower hardness, and a lower salt spray resistance and acid resistance; compared with Comparative Example 1, the non-volatile matter mass fraction, sag, adhesion and hardness of the coatings prepared in Examples 1-3 are significantly improved, and the hot and cold cycle period exceeds 250 hours without cracking, and the paint film has no blistering, rusting or peeling after being continuously immersed in a 25% sulfuric acid solution for 1500 hours, and the salt spray resistance is greater than 3000 hours.
[0032] In summary, the experimental results of Examples 1-3 and Comparative Examples 1-2 show that by mixing epoxy resin, polyphenol glycidyl ether compound and alkali-free glass fiber powder in a certain proportion, using epoxy curing agent and modified phenolic amine curing agent in a certain proportion as a curing agent system, and adding anti-rust fillers and additives, the coating of the present invention has a high solid content and a low VOCs content, can achieve the effect of high film thickness anti-sagging and good corrosion resistance and salt spray resistance, has high hardness and high adhesion, and has excellent crack resistance under low temperature conditions. It is suitable for scenes such as marine engineering steel structures, chemical machinery and equipment, and long transmission pipelines that require high film thickness corrosion protection and harsh outdoor ambient temperatures.
[0033] Although the terms such as epoxy resin, polyphenol glycidyl ether compound, solvent and alkali-free glass fiber powder are used more frequently in this article, the possibility of using other terms is not excluded. The use of these terms is only for more convenient description and explanation of the essence of the present invention; interpreting them as any additional limitation is contrary to the spirit of the present invention.
[0034] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-film thickness, crack-resistant, high-solid anticorrosive coating, characterized in that: The invention comprises component A and component B. Calculated by weight, the component A comprises 24-28 parts of epoxy resin, 6-8 parts of polyphenol glycidyl ether compound, 2.8-3.6 parts of auxiliary agent, 3.6-4.8 parts of alkali-free glass fiber powder, 37-41 parts of rust-proof filler and 3-4 parts of solvent; the component B comprises 10.1-10.9 parts of epoxy curing agent and 4.3-4.7 parts of modified phenolic amine curing agent.
2. The high-thickness, crack-resistant, high-solid anticorrosive coating according to claim 1, characterized in that: The epoxy resin is E-51 bisphenol A type epoxy resin, and its epoxy equivalent is 190-200.
3. The high-thickness, crack-resistant, high-solid anticorrosive coating according to claim 1, characterized in that: The polyphenol glycidyl ether compound is prepared by reacting plant polyphenols with epoxide in the presence of a quaternary ammonium salt catalyst; the epoxide equivalent of the polyphenol glycidyl ether compound is 280-320.
4. The high-thickness, crack-resistant, high-solid anticorrosive coating according to claim 1, characterized in that: The auxiliary agent includes 0.36-0.44 parts of defoaming agent, 0.27-0.33 parts of dispersant, 0.45-0.55 parts of rheological auxiliary agent and 1.8-2.2 parts of thixotropic agent.
5. The high-thickness, crack-resistant, high-solid anticorrosive coating according to claim 1, characterized in that: The defoamer is one or more combinations of vegetable oil defoamers and silicone defoamers; the dispersant is one or more combinations of BYK-180, BYK-190, Euka 690w, SN5040, and X-405; the rheological additive is organic bentonite; and the thixotropic agent is a polyamide thixotropic agent.
6. The high-thickness, crack-resistant, high-solid anticorrosive coating according to claim 1, characterized in that: The mesh number of the alkali-free glass fiber powder is 200-300 meshes, and the aspect ratio is 4-8:
1.
7. The high-thickness, crack-resistant, high-solid anticorrosive coating according to claim 1, characterized in that: In terms of weight, the anti-rust filler is prepared by mixing 15-16 parts of iron titanium powder, 12-13 parts of talc powder, 3-4 parts of precipitated barium sulfate and 7-8 parts of titanium dioxide.
8. The high-thickness, crack-resistant, high-solid anticorrosive coating according to claim 1, characterized in that: The solvent is a mixture of xylene and n-butanol in a mass ratio of 1.5-2.0:1.5-2.
0.
9. A method for preparing a high-thickness, crack-resistant, high-solid anti-corrosion coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: The preparation process of the component A is as follows: S1, adding epoxy resin, polyphenol glycidyl ether compound, solvent and defoamer, dispersant and rheological additive in proportion, stirring at a high speed of 1200-1500r / min for 15-20min by a high-speed disperser to evenly disperse the raw materials; S2. Add anti-rust filler and disperse at high speed at 3000-3200r / min for 30-40min; S3. Add alkali-free glass fiber powder and continue dispersing at 3000-3200r / min for 20-30min; S4, add thixotropic agent, disperse at 1200-1500r / min for 10-15min; S5, test fineness, viscosity, filter and package; The preparation process of the component B is as follows: S1. Add epoxy curing agent and modified phenolic amine curing agent in proportion, and disperse them evenly at 600-800r / min for 15-20min using a high-speed disperser; S2. Check viscosity and density, and packaging is completed.
10. Application of the high-thickness, crack-resistant, high-solid anticorrosive coating according to any one of claims 1 to 8 in marine engineering steel structures, chemical machinery and equipment, and long transmission pipelines, characterized in that: The mass ratio of component A to component B is 7.9-8.5:1.
Citation Information
Patent Citations
High-performance epoxy modified high-build anticorrosive paint and preparation method thereof
CN114479607A
Anticorrosive paint suitable for offshore photovoltaic truss and preparation method of anticorrosive paint
CN118308006A
Anti-corrosion material for sewage pool and preparation method and construction technology of anti-corrosion material for sewage pool
CN109401194A
High-solid low-viscosity universal primer and preparation method thereof
CN116179081A